Requiem for a rebel priest - Lim, Jr., Paulino (Quezon City, Philippines : New Day Publisher, 1996)
This novel (Sparrows Don't Sing in the Philippines) is a worth contribution to the growing body of fiction that attempts to re-examine our pat history in the light of our changing consciousness of the true meaning of our ideals and struggles as a nation." --Cirilo F. Bautista, Philippine Panorama. Lim is a master in recreating a milieu, and he returns those of us who lived thought the First Quarter Storm to that great epiphany, when it was clear who the villain's were but not so clear who the heroes were. As expected, Lim gives us a spellbinding story that is hard to put down.
Introit -- Dies Irae -- Recordare -- Lacrimosa -- Libera Me -- Agnus Dei.
Keywords: NOVELS -- PHILIPPINE FICTION